THE Factors Considered By PT Mandala Samudera Trans Semarang In Selecting Shipping Lines And Trucking Services To Export Dangerous Goods - Kurniani Kurniani; Paniya Paniya; Bagus Yunianto Wibowo; Laikhafil Qosim Munadzib fauzi; Rif’ah Rif’ah (International Journal of Economics, Business and Innovation Research, 2023)
This research aims to analyze the factors considered by PT Mandala Samudera Trans Semarang as a freight forwarder in choosing shipping lines and trucking services to export dangerous goods. The used research method is a qualitative research one. The data in this research are obtained by conducting interviews to 4 employees of company selected through purposive sampling technique. The obtained data is processed through the NVivo 12 software. The results in this study indicates that price (48.98%) is the main factor in choosing shipping lines to export dangerous goods. The service factor, i.e 37.70% is the factor for second consideration. The delivery factor is the fourth factor with a percentage of 13.11%. The last factor is reputation with a percentage of 8.20%. Meanwhile, the safety factor is the main factor in determining trucking services with a percentage of 35.17%. The second factor in choosing trucking services is the price factor with a percentage of 29.1%. The service factor of 27.08% and reputation of 8.33% are the next factors considered by PT Mandala Samudera Trans Semarang in choosing a trucking service company. Therefore, it is concluded that there are different factors in choosing shipping line and trucking services